Protocolo para la obtención de enzima invertasa a partir de hongos filamentosos y levaduras (2019)
Objective: To analyze the different techniques to obtain the invertase enzyme from yeasts and filamentous fungi, to propose a protocol that complies with the parameters necessary for its achievement. Methodology: A bibliographic search was carried out based on the research articles published in the last 10 years in databases such as Scielo, Science Direct, Springer and Google Academico. Results: a total of 185 articles were obtained, those were selected that were carried out experimental studies, studies that included the years 2009 to 2019, that would be the obtaining of the inverted enzyme from the yeasts and filamentous fungi, giving a total of 10 Articles found that meet the selection criteria for the development of the subject. Conclusion: this review, which will be published in the implementation techniques for obtaining the enzyme invertase from filamentous fungi and yeasts, these microorganisms are distributed in the environment, are easily accessible and can help reduce the costs of the elaboration. This is a guide of modifiable steps (protocol) by the researcher, because it is difficult to establish a homogeneous protocol for the great variety of methods and places of isolation, the amount of the inoculum, the fermentation cultures and the extraction technique. Regarding the determination of enzymatic activity on the contrary it is very similar to most articles, which means that it is reliable and give a confidence in the process